Optimizing Learning at IES Al-Ghuroba Elementary School: The Kampus Mengajar Program in Papua Barat Province - Raharja, Endra Putra; Amaliah, Raditha Harnum; Dasmasela, Chancy Genesa; Belau, Polikarlina; Fatmasari, Dwi (Journal of Social and Community Development, 2024)
The Kampus Mengajar program is an initiative by the Ministry of Education, Culture, Research, and Technology of Indonesia aimed at improving educational quality in the 3T (Disadvantaged, Frontier, and Outermost) regions. This study discusses implementing the 7th Kampus Mengajar program at IES Al-Ghuroba Elementary School, Sorong Regency, Papua Barat Daya. The program engaged university students as teaching agents to enhance students' literacy and numeracy skills through activities like 15-minute morning reading sessions, teaching aids in math lessons, and healthy living behavior campaigns. Results indicate significant improvements in student motivation, literacy and numeracy abilities, and social skills. Activities like technology adaptation and library revitalization also helped improve students' technological competencies and fostered a love for reading. Monitoring and evaluation by supervising lecturers and the Papua Barat Education Quality Assurance Agency (Balai Penjamin Mutu Pendidikan or BPMP Papua Barat) highlighted the program's positive impact on educational quality. The program's success underscores the importance of collaboration among students, lecturers, and school stakeholders in creating an enhanced learning environment. Continued support from the government and strengthened technology training is recommended for future program effectiveness.